2020
DOI: 10.1186/s12877-020-01624-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical and social environments on the risk of dementia among Taiwanese older adults: a population-based case-control study

Abstract: Background: Physical and social environments may influence cognition health in older adults. However, evidence regarding physical and social environments linked to dementia is lacking, especially in Asia. This study aims to explore the influence of physical and social environments on the incidence of dementia through a populationbased case-control design in Taiwan. Methods: We identified 26,206 incident cases with dementia aged≧65 years in 2010, with the same no. of controls from National Health Insurance clai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…The urbanization classification was proposed by Huang et al 18 They categorized all 358 cities and townships of Taiwan into five ordered levels of urbanization based on different indicators, including the number of residents, population density, and the percentage of people working in secondary and tertiary industries. 18,32,33…”
Section: Levels Of Urbanizationmentioning
confidence: 99%
“…The urbanization classification was proposed by Huang et al 18 They categorized all 358 cities and townships of Taiwan into five ordered levels of urbanization based on different indicators, including the number of residents, population density, and the percentage of people working in secondary and tertiary industries. 18,32,33…”
Section: Levels Of Urbanizationmentioning
confidence: 99%
“…However, such a holistic perspective is fairly new in the evolving concept of brain health. 16 Only in recent years, researchers started to investigate environmental impacts on dementia development, with air and noise pollution [17][18][19] and the built and green environment [20][21][22] being considered as potential factors. For example, Liu et from health insurance claims in older Taiwanese citizens and linked it to environmental measures: odds for dementia were lower in environments with more playgrounds, sports venues and community centers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Liu et from health insurance claims in older Taiwanese citizens and linked it to environmental measures: odds for dementia were lower in environments with more playgrounds, sports venues and community centers. 22 Wu et al investigated environmental aspects and dementia risk in the HIC-cohort Cognitive Function and Ageing Study (CFAS II) from the UK as well as in the LMIC-cohort 10/66 study: living far from daily amenities was associated with higher odds for dementia in both studies, while living far from lifestyle and healthcare amenities was associated with increased odds of dementia only in the 10/66 study, and living far from public parks with lower odds of dementia in CFAS II. 23 Epidemiological findings have yet to be translated into risk reduction interventions.…”
Section: Introductionmentioning
confidence: 99%
“…As the skewness still appeared after using several transformation methods, we thus categorized the study variables into groups to lower the misclassification for normality. Thus, all study variables were divided by tertiles (low, medium, and high) and the lowest served as the reference group [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Scarce studies have examined the relationships between social-economic environments and depression. Only two recent studies by Liu et al (2020) and Liu (2021) were found to investigate the effects of social-economic environments on health, where their outcome variables were dementia and mortality, while the social-economic indicators differed from a case to another [13,14].…”
Section: Introductionmentioning
confidence: 99%